2019
DOI: 10.5603/arm.2019.0014
|View full text |Cite
|
Sign up to set email alerts
|

Hypersensitivity Pneumonitis Recognised in a Single Pulmonary Unit, between 2005 and 2015: Comparison with Recently Proposed Diagnostic Criteria

Abstract: Introduction: Hypersensitivity pneumonitis (HP) is the third most common interstitial lung disease after idiopathic pulmonary fibrosis and nonspecific interstitial pneumonia. Pathogenesis of HP is related to repeated exposure to inhaled environmental antigens that sensitise the susceptible, genetically predisposed persons. The aim of the present retrospective study was to summarise the diagnostic methods used in consecutive patients with HP, recognised in a single pulmonary unit, between 2005 and 2015, and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 20 publications
2
8
1
Order By: Relevance
“…This degree of variability is perhaps not surprising, considering the lack of a standardised national approach to establishing HP causation. While the true epidemiology of HP in Britain remains unknown, the range of estimates from the GB HP survey were broadly consistent with the findings from other studies, where the proportion of HP patients without an identifiable cause was: 0% in Japan14; 4% in Brazil15; 6% in Poland16; 28% in China17; and 25%–63% in the USA 10–13…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…This degree of variability is perhaps not surprising, considering the lack of a standardised national approach to establishing HP causation. While the true epidemiology of HP in Britain remains unknown, the range of estimates from the GB HP survey were broadly consistent with the findings from other studies, where the proportion of HP patients without an identifiable cause was: 0% in Japan14; 4% in Brazil15; 6% in Poland16; 28% in China17; and 25%–63% in the USA 10–13…”
Section: Discussionsupporting
confidence: 86%
“…For domestic HP, the most commonly suspected exposures are to birds, bird droppings or feathers. This is in keeping with the majority of studies from other countries, where avian exposure has been the most commonly identified cause, accounting for 17%–66% of all cases 10–12 14 16 17 24. A recent retrospective single-centred US study also noted a high prevalence of contact with avian protein in biopsy proven chronic HP cases (29% to bird and 58% to down), and incorporated a history of exposure into a prediction model 4.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Clinical presentation, imaging studies, and laboratory testing results of 94 patients, 49 females, 45 males, mean age 52 (±12) years, with newly recognized HP, were analyzed retrospectively. The applied diagnostic criteria of HP recognition have been described previously [13,14] and consisted of:…”
Section: Methodsmentioning
confidence: 99%
“…In case of diagnostic difficulties, the lack of exposition, non-characteristic HRCT pattern, or lack of lymphocytosis in BAL, lung biopsy was performed. The details of HP diagnostic pathway in the presented group of patients, have been described previously [11].…”
Section: Methodsmentioning
confidence: 99%